Microorganisms and Biotechnology - Taylor, Jane, 1950-; University of Bath. (Cheltenham : Nelson Thornes, 2001)
Written to cover the revised Advance Level specifications, this revised edition covers the nature and biology of micro-organisms, together with an extensive discussion of industrial use and their importance in health and diseases.
Previous ed.: Cheltenham: Thomas Nelson, 1992.
Ill. on inside cover.
Includes bibliographical references (p. 179) and index.
Keywords: Microorganisms; Microorganisms -- Problems, exercises, etc; Microbial biotechnology; Microbial biotechnology -- Problems, exercises, etc; Biotechnological microorganisms; Biotechnological microorganisms -- Problems, exercises, etc; Popular Science and Nature